Kaempferia galanga L. A Medicinal Plant Used By Indonesian Ethnic Groups: Genetic Diversity Based on Inter-Simple Sequence Repeats (ISSR) - Dyah Subositi; Nina Kurnianingrum; Rohmat Mujahid; Yuli Widiyastuti (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
Kencur (Kaempferia galanga L.) has been recognized as a medicinal plant used by many ethnic groups in Indonesia. Up to present time, information on the diversity of the respected plant is still limited. The aim of this research was to reveal the genetic diversity of K. galanga in Indonesia as a baseline medicinal plant database. Inter-Simple Sequence Repeat (ISSR) molecular markers were employed to analyze the genetic diversity information of K. galanga from 12 selected locations in Indonesia where ethnic groups used the plant. Dice index similarity was used to calculate a similarity index, and Unweighted Pair Group Method Using Arithmetic Mean (UPGMA) was used to constructing a dendrogram. Ten selected ISSR primers generated 104 amplified DNA fragments, of which 98 fragments (94.2%) were polymorphic. The genetic similarity index among accessions ranged from 49.6–93.3%, indicating a high level of genetic diversity in K. galanga. The ISSR markers were thus able to genetically differentiate K. galanga accessions.